Analysis of Flame Characteristics in a Laboratory-Scale Turbulent Lifted Jet Flame via DNS. (September 2013) - Wang, Haiou; Luo, Kun; Yi, Fuxing; Fan, Jianren
A fully compressible 3D solver for reacting flows has been developed and applied to investigate a turbulent lifted jet flame in a vitiated coflow by means of direct numerical simulation (DNS) to validate the solver and analyze the flame characteristics. An eighth-order central differencing scheme is used for spatial discretization and a fourth-order Runge-Kutta method is employed for time integration. The DNS results agree well with the experimental measurements for the conditional means of reactive scalars. However, the lift-off height is under predicted. The mean axial velocity develops into a self-similar profile after x/D = 6. The normalized flame index is employed to characterize the combustion regime. It is found that at the flame base the gradients of the reactants are opposed and diffusion combustion is dominant. Further downstream, the contribution of premixed combustion increases and peaks at x/D = 8. Finally, the stabilization process is examined. The turbulent lifted flame is proved to stabilize in the lean mixtures and low scalar dissipation rate regions.